Real Time Feedback in English Microteaching Practice: A Case Study on Online Learning - Nurul Hidayah; Lilia Indriani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
Online microteaching classes allow the student to practice their teaching ability using the online platform. This case study attempted to find out the perspective of teacher trainees using real-time feedback and peer observation of online microteaching classes. The researcher focused on 3rd year microteaching students in 2020/2021 at one of Indonesia's state universities. In this qualitative case study, the researcher used multiple data collection techniques. The researcher uses a questionnaire from (Eksi, 2020) with some changes to suit the purpose of this study in collecting data. The researcher distributed the questionnaire to 40 teacher trainees who already practiced online microteaching and got real-time feedback from the lecture and their peers. The teacher trainee showed a positive perspective in using real-time feedback. They thought the process helped increased their professional development. Many student-teachers were engaged in giving real-time feedback to other student teacher's performance. They realized that real-time feedback helped them positively. However, the results found that most of the teacher trainees believe that the direct observation from two or three students was enough. Teacher trainees also thought that online classes are increasing the opportunity for misunderstanding.